Hemodialysis for the Treatment of Severe Accidental Hypothermia. Issue 3 (9th October 2013) - Singh, Tripti; Hallows, Kenneth R.; Rodby, Roger A.
Abstract Severe hypothermia is defined as a core body temperature <28°C and is associated with in‐hospital mortality rates of 50% or higher. Delays in rewarming and slower rates of rewarming are the most important prognostic factors associated with increased mortality. Arrhythmias are the most common cause of mortality in patients with severe accidental hypothermia. Electrolyte abnormalities such as hyperkalemia and hypocalcemia that may worsen when patients are rewarmed contribute to the risk of arrhythmias. Cardiopulmonary bypass (CBP) is considered the treatment of choice for active internal rewarming of patients with severe hypothermia, but it is not always available and is time consuming to initiate. We describe a case where hemodialysis (HD) was used to treat accidental hypothermia in a patient with an initial temperature of 23.5°C. Average rewarming rates of 1.5°C/hour were achieved. The advantages of HD when compared with CBP are that it is (1) more widely and readily available, (2) less invasive, (3) less expensive, and (4) can correct associated acidosis and electrolyte abnormalities commonly seen in patients with severe hypothermia.